Fate of Histoplasma capsulatum in Guinea Pig Polymorphonuclear Leukocytes - Howard, Dexter H. (1973)
Guinea pig polymorphonuclear leukocytes (PMN) were parasitized in vitro with yeast cells of Histoplasma capsulatum. Preparations stained after 3 h at 37 C with May Greenwald-Giemsa revealed that 87% of the yeasts were tinctorially altered. Such alterations corresponded to those displayed by fungus cells intentionally killed by heat or other means and thus the altered yeast were presumed to be dead. A combination of 10(−5) M H(2)O(2), 10(−5) M KI, and horseradish peroxidase killed H. capsulatum. Death was assessed by the eosin-y dye exclusion test. All of the listed components were required for death of the fungus. A granule lysate preparation derived from guinea pig PMN leukocytes could replace the horseradish peroxidase in the fungicidal system. The granule lysates behaved in keeping with the attributes of a myeloperoxidase. Thus, PMN leukocytes and certain extracellular peroxidase systems kill the yeast cell phase of the dimorphic fungus H. capsulatum.